Acute Respiratory Infections (ARI) in Toddlers: A Review of Contributing Risk Factors - Nurila Safar; Suharto Suharto; Sitti Nurhidayanti (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
Acute Respiratory Infections (ARI) are infectious diseases that affect both the upper and lower respiratory tracts, ranging from mild to severe conditions, and can potentially lead to death, especially in children under five. This study aims to determine the factors associated with the incidence of ARI among children under five in the working area of Puskesmas Perawatan Tiley in 2023. This was an analytical quantitative study using a cross-sectional approach. The population consisted of 266 mothers of children under five. A total of 73 respondents were selected using proportional random sampling. Data were analyzed using the Chi-square test. The findings showed significant associations between ARI incidence and exposure to cigarette smoke (P=0.000≤0.1), air ventilation (P=0.018≤0.1), and housing density (P=0.000≤0.1). However, there was no significant association between immunization status (P=0.726≥0.1) and ARI incidence. It is recommended that the health center strengthen health promotion efforts related to ARI prevention and educate the community on healthy housing conditions, particularly concerning adequate ventilation, avoiding overcrowding, and the dangers of cigarette smoke exposure to children.